2008
DOI: 10.1016/j.micinf.2008.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent gastro-intestinal nematode infection does not alter the development of experimental cerebral malaria

Abstract: Concurrent helminth infections have been suggested to be associated with protection against cerebral malaria in humans, a condition characterised by systemic inflammation. Here we show that a concurrent chronic gastro-intestinal nematode infection does not alter the course of murine cerebral malaria. Mice infected with Heligmosomoides polygyrus, and co-infected with Plasmodium berghei ANKA 14 days later, developed malaria parasitemia, weight loss and anemia, at the same rate as mice without nematode infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…In some animal models, helminth/malaria co-infected animals have been protected against severe malaria (18), whereas other studies report an increased susceptibility to severe disease (17) or no effect on severe disease whatsoever (56). More recently, Heligmosomoides polygyrus -infected mice immunized with blood-stage parasites of P. chabaudi chabaudi AS produced lower levels of malaria-specific Ab and of malaria-specific IFN-γ but higher levels of IL-4, IL-13, IL-10, and TGFβ (57), while others, using a similar model, showed that concurrent H. polygyrus had no effect on the development of cerebral malaria (56). …”
Section: Discussionmentioning
confidence: 99%
“…In some animal models, helminth/malaria co-infected animals have been protected against severe malaria (18), whereas other studies report an increased susceptibility to severe disease (17) or no effect on severe disease whatsoever (56). More recently, Heligmosomoides polygyrus -infected mice immunized with blood-stage parasites of P. chabaudi chabaudi AS produced lower levels of malaria-specific Ab and of malaria-specific IFN-γ but higher levels of IL-4, IL-13, IL-10, and TGFβ (57), while others, using a similar model, showed that concurrent H. polygyrus had no effect on the development of cerebral malaria (56). …”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with Hp-Pb ANKA 2 weeks after initial helminthic infection did not modify the development of ECM despite accelerated Pb growth in vivo [149]. Likewise, other results from the same model of coinfection in BALB/c and C57BL/6 mice showed no differences in parasitemia, anemia, or body weight in relation to mice infected only with Plasmodium [150]. Therefore, Hp infection does not affect the outcome of Pb ANKA (Table 4(b)).…”
Section: Experimental Models Of Coinfectionmentioning
confidence: 99%
“…Therefore, when the other studies have found that adults with worms are still protected, we contend that this corresponds mostly to adults with comparatively lower worm loads who have achieved clinical immunity anyway. In support of this view, most studies of experimental co-infections in models, in which the worm load is usually high since it is an induced infection, concluded to their deleterious influence upon malaria [19], [20], [21], [22], with a single exception in a rodent model of cerebral malaria [23].…”
Section: Introductionmentioning
confidence: 98%